Development of XYZ University's Student Admission Site Using Waterfall Method - Raden Muhamad Firzatullah (Jurnal Mantik, 2021)
The purpose for this research is to make a blueprint of State University Of Jakarta website for admission of new students. This site using RestFul API Web Service technology that split in between data processing logic system and user interface so that if the system are in development, developer no need to rebuild or reorganize the whole part of system. The research done at Information and Technology Center (PUSTIKOM) University of XYZ on February until May 2016. Developing method that used are software method development. i.e. spiral development method. Overall there’s 3 main stages of this research and development. There are (1) early research; (2) product development; (3) test and revision of the product. Early research done for identify the problem and search the easy solution for solve that matter. Testing process for the prototype of the product done with media expert test. Data collecting process done by using questionaire which then analyzed with desciptive and quantitative technique. Based on research, testing result show that prototype have 100% score on Validation Test. Based the test result, the blueprint of University Of XYZ website for admission of new students that have been developed declared eglible for use as a milestone of admission of new students system for University of XYZ in a next year.